Vegetation classification algorithm using convolutional neural network ResNet50 for vegetation mapping in Bandung district area - Rina Pudji Astuti; Ema Rachmawati; Edwar Edwar; Simon Siregar; Indra Lukmana Sardi; Arfianto Fahmi; Yayan Agustian; Agus Cahya Ananda Yoga Putra; Faishal Daffa (JURNAL INFOTEL, 2022)
Bandung District is one of crop provider for West Java Province. About 31.158,22 ha is used for crop. However, some of them are not maintained well due to lack of vegetation map information. Local authority has tried to map the vegetation in their area by using free license satellite images, and aerial images from Unmanned Aerial Vehicle (UAV). Despite both images being able to provide large plantation area images, both are unable to classify the vegetation type in those images. Telkom University with Bandung Agriculture Regional Office (Dinas Pertanian Kabupaten Bandung) has conducted joint research to develop algorithm based on 50-layer residual neural network (ResNet50) to classify the vegetation type. The input is of this algorithm is primarily aerial images are captured from different type, height, and position of crops. Seven different ResNet50 configurations have been set and simulated to classify the crop images. The result is the configuration with resized images, employing triangular policy of cyclic learning rate with rate 1.10−7 – 1.10−4 comes out as the best setup with more than 95% accuracy and relatively low loss.